Pemanfaatan Tandan Kosong Kelapa Sawit Sebagai Bahan Baku Briket Dengan Perekat Tepung Kanji - anna dhora; Antonius Sihotang (Jurnal Sains dan Ilmu Terapan, 2022)
Abstract— Oil palm empty fruit bunches (TKKS) are one of the solid wastes produced from the processing of palm oil. The most use of this type of waste is as fertilizer and ground cover or natural mulch. Another alternative for the use of OPEFB is as a raw material for making briquettes, which can be used as a substitute for firewood which has the advantage of being environmentally friendly. This study aims to determine the effect of starch adhesives on the manufacture of EFB briquettes with the addition of rubber seed shells. The process of making briquettes consists of the stages of preparing raw materials, composing, grinding charcoal, making adhesives, making briquette dough, printing, pressing, drying and testing briquettes. The results of the tests carried out for the adhesive variation of 9.8% showed a water content value of 7.16%, an ash content of 6.04%, and a density of 0.440 g/cm3. All the test results have met SNI 01/6235/2000.